The arrival of the invasive tubeworm Ficopomatus enigmaticus (Fauvel, 1923) (Annelida: Serpulidae) to the Azores, possibly via migratory birds - Costa, Ana; Parente, ManuelaI.; de Frias Martins, António M. (BioInvasions Records, 2019)
The non-indigenous polychaete Ficopomatus enigmaticus, also known as the Australian tube worm, was recorded from Paul da Praia da Vitória (Praia da Vitória Marsh), Terceira island (Azores) in July 2016. This is the first record of this species on the Atlantic islands of the Macaronesia biogeographical region. At present, F. enigmaticus is exclusively in the lagoon of Paul da Praia where it is established and exhibits invasive behaviour. To explain the arrival of F. enigmaticus in this wetland system, which is not directly connected to the sea, we hypothesize natural mediated dispersal through migratory bird phoresy. This vector is crucial to consider in terms of risk assessments as this species spreads to other ecologically fragile areas. Potential impacts of F. enigmaticus on these sensitive and rare systems in the region are discussed.
World Polychaeta Database (WPolyDb)